How are eczema 'flares' defined? A systematic review and recommendation for future studies. (1st March 2014) - Langan, S.M.; Schmitt, J.; Williams, H.C.; Smith, S.; Thomas, K.S.
Summary: Eczema is an important public health problem due to high prevalence and associated morbidity. As a chronic, relapsing disease, the ability to capture disease flares is important when evaluating treatment success, yet it is unclear how flares should be defined. This study systematically reviews and critically appraises the literature defining flares in eczema, and explores methodological and practical aspects of including eczema flares as outcome measures in trials to inform developing an international consensus definition adding details of our own recent experience. A systematic review was undertaken of flare definitions in prospective intervention studies of eczema published up until 14 February 2013. Data were double‐extracted. We pre‐specified that important characteristics of a good flare definition should include (i) being feasible to collect and (ii) being recorded at the time flare symptoms were experienced. Three hundred and fourteen papers were identified of which 26 included some description of eczema flares. Overall, 22 different flare definitions were used. Flares were included as the primary outcome in 17 studies (65%). Only four studies (15%) used a patient‐reported flare definition. No studies fulfilled all of our pre‐specified essential characteristics. No validation studies were identified. The wide variation and lack of validation of flare definitions hampers comparison of findings between studies for this chronic, relapsing disease. None of the currently used definitions seem fit for purpose. Further research should establish which aspects of worsening of disease are most important to patients, and how best to capture these data in a way that is valid, reliable and feasible in all clinical and research settings.